OP0339 TOCILIZUMAB IN GIANT CELL ARTERITIS. MONOTHERAPY VERSUS COMBINED WITH CONVENTIONAL IMMUNOSUPPRESSIVE DRUGS. (June 2019) - Calderón-Goercke, Monica; Loricera, J.; Prieto-Peña, D.; Aldasoro, Vicente; Castañeda, Santos; Villa-Blanco, Ignacio; Humbría, Alicia; Moriano, Clara; Romero-Yuste, Susana; Narváez, J.; Gomez-Arango, Catalina; Perez-Pampín, Eva; et al.
Abstract : Background: Giant cell arteritis (GCA) can be refractory to corticosteroid therapy. Tocilizumab (TCZ) has been approved in the treatment of GCA. There are no studies comparing the efficacy and safety when using TCZ as monotherapy or in combination with conventional immunosuppressive drugs in GCA. Objectives: Our aim was to compare efficacy and safety of TCZ combined or in monotherapy in GCA. Methods: Multicenter study on 134 patients with refractory GCA who received TCZ therapy as monotherapy or combined with conventional immunosuppressants. Prolonged remission, absence of clinical symptoms and signs and normalization of the acute phase reactants for at least 6 months. Relapse, recurrence of signs or symptoms of GCA and/or ESR >20 mm/h in men or >25 mm/h in women, and/or serum CRP >0.5 mg/dL related to GCA, both before and after starting TCZ therapy. Results: We evaluated 134 patients (101 w/33 m) with a mean age of 73.0±8.8 years. TCZ was prescribed as monotherapy in 82 (62.2%) cases and combined with conventional immunosuppressants in 52 (38.8%) patients: MTX (n=48), AZA (n=3), and LFN (n=1). A comparative study between both groups is summarized in TABLE . Patients who received combined TCZ were younger and had a higher C-reactive protein (CRP) and a higher presence of aortitis in imaging techniques. After TCZ was started, prolonged remission was reached with combined therapy (statistical significance at 12 and 24 months). The corticosteroids sparing effect was similar in both groups. And in terms of side effects no significant difference was seen between TCZ as monotherapy or combined with conventional immunosuppressants. Conclusion: Patients receiving combined conventional immunosuppressants with TCZ in the clinical practice study showed a higher prolonged remission. The incidence of serious infections and/or relevant adverse events was not affected according to the treatment. As well as the corticoid-sparing effect was achieved in the same way in both groups. References: [1] Goercke .Calderón-M. Tocilizumab in giant cell arteritis. Observational, open-label multicenter study of 134 patients in clinical practice. Semin Arthritis Rheum. 2019 Jan 5. pii: S0049-0172(18)30571-7. doi: 10.1016/j.semarthrit.2019.01.003. [Epub ahead of print] [2] Loricera J et al. Semin Arthritis Rheum.2015;44:717-723